Diagnostic sensitivity of Tc‐99m HYNIC PSMA SPECT/CT in prostate carcinoma: A comparative analysis with Ga‐68 PSMA PET/CT. Issue 11 (26th June 2017) - Lawal, Ismaheel O.; Ankrah, Alfred O.; Mokgoro, Neo P.; Vorster, Mariza; Maes, Alex; Sathekge, Mike M.
Abstract : Background: Emerging data from published studies are demonstrating the superiority of Ga‐68 PSMA PET/CT imaging in prostate cancer. However, the low yield of the Ge‐68/Ga‐68 from which Gallium‐68 is obtained and fewer installed PET/CT systems compared to the SPECT imaging systems may limit its availability. We, therefore, evaluated in a head‐to‐head comparison, the diagnostic sensitivity of Ga‐68 PSMA PET/CT and Tc‐99m PSMA SPECT/CT in patients with prostate cancer. Methods: A total of 14 patients with histologically confirmed prostate cancer were prospectively recruited to undergo Ga‐68 PSMA PET/CT and Tc‐99m HYNIC PSMA SPECT/CT. The mean age of patients was 67.21 ± 8.15 years and the median PSA level was 45.18 ng/mL (range = 1.51‐687 ng/mL). SUVmax of all lesions and the size of lymph nodes with PSMA avidity on Ga‐68 PSMA PET/CT were determined. Proportions of these lesions detected on Tc‐99m HYNIC PSMA SPECT/CT read independent of PET/CT findings were determined. Results: A total of 46 lesions were seen on Ga‐68 PSMA PET/CT localized to the prostate ( n  = 10), lymph nodes ( n  = 24), and bones ( n  = 12). Of these, Tc‐99m HYNIC PSMA SPECT/CT detected 36 lesions: Prostate = 10/10 (100%), lymph nodes = 15/24 (62.5%), and bones = 11/12 (91.7%) with an overall sensitivity of 78.3%. Lesions detected on Tc‐99m HYNIC PSMA SPECT/CT were bigger in size ( P  < 0.001) and had higher SUVmax ( P  < 0.001) as measured on Ga‐68 PSMA PET/CT compared to those lesions that were not detected. All lymph nodes greater than 10 mm in size were detected while only 28% of nodes less than 10 mm were detected by Tc‐99m HYNIC PSMA SPECT/CT. In a univariate analysis, Lymph node size ( P  = 0.033) and the SUVmax of all lesions ( P  = 0.007) were significant predictors of lesion detection on Tc‐99m HYNIC PSMA SPECT/CT. Conclusion: Tc‐99m HYNIC PSMA may be a useful in imaging of prostate cancer although with a lower sensitivity for lesion detection compared to Ga‐68 PSMA PET/CT. Its use is recommended when Ga‐68 PSMA is not readily available, in planning radio‐guided surgery or the patient is being considered for radio‐ligand therapy with Lu‐177 PSMA. It performs poorly in detecting small‐sized lesions hence its use is not recommended in patients with small volume disease.